Contextualizing the socio-economic and spatial patterns of using menstrual hygienic methods among young women (15–24 years) in India: A cross-sectional study using the nationally representative survey - Swagata Karjee; Margubur Rahaman; Prites Chandra Biswas (Clinical Epidemiology and Global Health, 2023)
Background: Utilizing hygienic methods during the menstrual cycle reduces women's health vulnerabilities and promotes their overall well-being. However, the usage of unsanitary menstrual methods is sizable among young women in India. Therefore, the current study aims to determine the socioeconomic and geographic distribution and predictors of using menstrual hygiene methods among Indian women. Methods: The present study used secondary data, i.e., the National Family Health Survey-5 (2019–2021). The total sample of the study consisted of 241,180 young women aged 15–24 years. Descriptive statistics, bivariate analysis with the Pearson chi-square significant test, and multivariate analyses were applied to accomplish the study objectives. Results: In India, about 77% of women utilized hygienic menstrual methods. However, there were significant sociocultural and geographic differences in sanitary menstruation procedures. Menstruation hygiene practices were far less common in India's socioeconomically underperforming districts. Age, education level, social status, religion, place of residence, and geographic region were discovered to be significant factors in utilizing hygienic menstruation techniques. Women's exposure to mass media, autonomy, and household wealth were determined to be motivating factors for using clean menstrual procedures. Conclusion: Majority of young women adopted hygienic menstrual methods, yet socioeconomic and geographic inequalities still raise questions. Therefore, the population and spatial stratification strategies should be used to diminish regional heterogeneity and encourage the use of hygienic menstruation practices by all. Further study is encouraged to investigate how behavioral and socioeconomic factors influence menstrual choice and practice in India using qualitative research approaches.